Japans Soft Power and its effect on Iceland - Svavar Páll Guðgeirsson 1986- (2014)
With the rising popularity of Japanese Culture, there have been many people that have been influenced by it. How come that The Japanese government is so successful with their Soft Powers compared to many other nations? And how come that Iceland, a little island located in the Atlantic Ocean, is getting so affected by Japans Soft Power. What the researcher is hoping to answer in this paper is how come Japan is able to increase their influence so much with just Soft Powers, and if there could be any specific reason that can explain Japans increasing influence on Iceland.